Reliability of the Handgrip Strength Test in Elderly Subjects With Parkinson Disease. (March 2016) - Villafañe, Jorge H.; Valdes, Kristin; Buraschi, Riccardo; Martinelli, Marco; Bissolotti, Luciano; Negrini, Stefano
Background: The handgrip strength test is widely used by clinicians; however, little has been investigated about its reliability when used in subjects with Parkinson disease (PD). The purpose of this study was to investigate the test-retest reliability of the handgrip strength test for subjects with PD.Methods: The PD group consisted of 15 patients, and the control group consisted of 15 healthy subjects. Each patient performed 3 pain-free maximal isometric contractions on each hand on 2 occasions, 1 week apart. Intraclass correlation coefficient (ICC), standard error of measurement (SEM), and 95% limits of agreement (LOA) were calculated. The 2-way analysis of variance (ANOVA) was conducted to determine the differences between sides and groups.Results: Test-retest reliability of measurements of grip strength was excellent for dominant (ICC = 0.97; P = .001) and non-dominant (ICC = 0.98; P = .001) hand of participant with PD and (ICC = 0.99; P = .001) and (ICC = 0.99; P = .001) respectively, of healthy group.Conclusions: The Jamar hand dynamometer had fair to excellent test-retest reliability to test grip strength in participants with PD.